2015
DOI: 10.1111/1365-2656.12387
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related effects of chronic hantavirus infection on female host fecundity

Abstract: Summary1. Pathogens often cause detrimental effects to their hosts and, consequently, may influence host population dynamics that may, in turn, feed back to pathogen transmission dynamics. Understanding fitness effects of pathogens upon animal host populations can help to predict the risks that zoonotic pathogens pose to humans. 2. Here we determine whether chronic infection by Puumala hantavirus (PUUV) affects important fitness-related traits, namely the probability of breeding, reproductive effort and mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Such complex relationships between parasite infection and host fitness were indeed observed in other rodent-borne diseases. For example, infection of Puumala hantavirus in bank voles ( Myodes glareolus ) was initially assumed to be asymptomatic [5153] but recent long-term field studies observed negative effects on the survival probability and an equivocal impact on the fecundity of females [36, 54, 55]. An important difference between Old World arenaviruses and hantaviruses, however, is that the latter causes persistent infections in their reservoir hosts [56], while the former infects their hosts mainly acutely [29, 43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such complex relationships between parasite infection and host fitness were indeed observed in other rodent-borne diseases. For example, infection of Puumala hantavirus in bank voles ( Myodes glareolus ) was initially assumed to be asymptomatic [5153] but recent long-term field studies observed negative effects on the survival probability and an equivocal impact on the fecundity of females [36, 54, 55]. An important difference between Old World arenaviruses and hantaviruses, however, is that the latter causes persistent infections in their reservoir hosts [56], while the former infects their hosts mainly acutely [29, 43].…”
Section: Discussionmentioning
confidence: 99%
“…This might be likely, as it has been shown that LCMV can severely disrupt hormonal regulation in laboratory mice [25, 65, 66]. Similarly, Kallio et al [36] suggest that infection with Puumala hantavirus enhances breeding in young female bank voles, but not in old ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bank vole, Myodes glareolus, is the specific reservoir host of the hantavirus Puumala (PUUV), the causative agent of nephropathia epidemica (NE) in humans (Brummer-Korvenkotio, Henttonen, & Vaheri, 1982). In M. glareolus, PUUV infections are chronic (Hardestam et al, 2008;Voutilainen et al., 2015) and mainly asymptomatic (Bernshtein et al, 1999), although small negative effects on the fitness of the host have been reported (Kallio et al, 2007;Kallio, Helle, Koskela, Mappes, & Vapalahti, 2015;Tersago, Crespin, Verhagen, & Leirs, 2012). The tolerance of rodents to hantavirus infections has mostly been examined by comparing the immune response between reservoir and non reservoir hosts (see for reviews Easterbrook & Klein, 2008, Schountz & Prescott, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast with laboratory rats (Pinheiro, Salvucci, Aguila, & Mandarim‐de‐Lacerda, ), where protein restriction increased F2's mass at birth and decreased male F2 adult body mass. While we did not find intergenerational effects due to protein restriction, we might have overlooked other phenotypic traits, such as pathogen susceptibility (Monaghan, ), which can affect fitness‐related traits in F2 besides winter survival, for example reproduction (Hakkarainen et al, ; Kallio, Helle, Koskela, Mappes, & Vapalahti, ; Mills, ). We propose that a protein‐restricted early life impacts bank vole phenotype, but it is of little consequence to fitness in natural settings.…”
Section: Discussionmentioning
confidence: 82%